2015
DOI: 10.1111/ctr.12636
|View full text |Cite
|
Sign up to set email alerts
|

Early immunosuppression treatment correlates with later de novo donor‐specific antibody development after kidney and pancreas transplantation

Abstract: The risk of post-transplant dnDSA development correlates with early immunosuppressive management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Data from a recently published prospective and randomized study showed that immediate use of sirolimus after SPK transplantation, in the context of CNI‐free immunosuppression, is associated with an increased rate of surgical complications 277 . Additionally, the use of m‐TOR inhibitors in the setting of CNI‐free immunosuppression could increase the formation of DSA 289 . This issue is not fully addressed in the literature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Data from a recently published prospective and randomized study showed that immediate use of sirolimus after SPK transplantation, in the context of CNI‐free immunosuppression, is associated with an increased rate of surgical complications 277 . Additionally, the use of m‐TOR inhibitors in the setting of CNI‐free immunosuppression could increase the formation of DSA 289 . This issue is not fully addressed in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…277 Additionally, the use of m-TOR inhibitors in the setting of CNI-free immunosuppression could increase the formation of DSA. 289 This issue is not fully addressed in the literature. Reported outcomes range from no effect, 290 to increased development on nondonor-specific HLA antibodies, with immediate evidence of worse graft outcome, 291 and to an increased incidence of de novo DSA anti-class II HLA agents at 1 year after transplantation.…”
Section: M-tor Inhibitorsmentioning
confidence: 99%
“…In a phase 3 single cohort study of islet-afterkidney (IAK) transplantation involving 24 participants, the rate of de novo sensitization was up to 22% (5 of 23) over 3 years, 17 which is in fact similar to, and not greater than, that reported in simultaneous pancreas-kidney transplantation (SPK) (21.3%). 18 Outcomes of pancreas or islets with kidney transplantation in T1DM were compared in a nonrandomized single center retrospective analysis. 19 The 5-year insulin independence rate was higher with SPK/PAK (73.6% vs 9.3% with SIK/IAK), and posttransplant HbA 1c levels were lower (7.8%-5.9% vs 8.0%-6.5% with SIK/IAK).…”
Section: Pancreas or Islet Transplantationmentioning
confidence: 99%